(untitled) (Studia Prawnicze / The Legal Studies, 2006)
Szeroko rozumiane mechanizmy mediacyjno-koncyliacyjne, prowadzące w efekcie do ugodowego załatwienia sporu, stanowią stały element procedur prawa międzynarodowego publicznego. Ta wyraźna preferencja w zakresie ugodowego rozwiązywania konfliktów w wymiarze międzynarodowym nie wymaga - jak się wydaje - poszukiwania dodatkowych przyczyn dla jej uzasadnienia. Zalety tego sposobu załatwiania sporów są bezdyskusyjne, a co więcej, zaznaczają się one w ciągle niezwykle delikatnej sferze suwerenności państw. Skuteczne osiągnięcie w drodze polubownej zgodnego porozumienia stron konfliktu co do sposobu jego rozwiązania nie może zatem znajdować konkurencji w stosowaniu mechanizmów opartych na elementach przymusu prawnego. In this article the authors consider the institution of friendly settlement which is covered by the control mechanism of the European Convention for the Protection of Humań Rights and Fundamental Freedoms of 1950 (ECHR). Being this a traditional mechanim of conflict solution which can be found in the odginał version of the ECHR the friendly settlement has undergone an important evolution as far as its role and practical results are concerned. The authors start with the reconstruction of the normative standards in the field and then present the institution against the background of the chosen Strasbourg case-law. According to the authors the above-mentioned evolution of friendly settlement can be particularly noticed in the morę freąuent combination of individual and collective benefits that can be obtained in this way. The authors argue that in the light of the present-day situation of the Strasbourg control procedurę friendly settlement reached between the parties of the conflict can be seen as a very useful instrument not only for the reparation of a particular injury but also for the improvement of the domestic law or practice. For obvious reasons a special attention was paid to the Polish cases (a.o. case of Broniowski v. Poland) which are an adeąuate illustration of the main thesis formulated by the authors.